Clinicopathological study of hepatic mesenchymal hamartoma and undifferentiated embryonal sarcoma of the liver: a single center study from Iran - Parham Habibzadeh; Mohaddese Ansari Asl; Hamid Reza Foroutan; Ali Bahador; Mohammad Hossein Anbardar (BMC, 2021)
Abstract Background Undifferentiated embryonal sarcoma of liver (UESL) and hepatic mesenchymal hamartoma (HMH) are two rare entities which mainly affect the pediatric population. The aim of this investigation was to provide a comprehensive overview of the clinicopathologic characteristics of the patients diagnosed with these two conditions in a tertiary referral center in Iran. Methods In this retrospective study patients diagnosed with UESL or HMH between 2012 and 2020 were studied. A comprehensive histopathologic evaluation of the cases along with immunohistochemistry evaluation using a panel of antibodies was conducted. Furthermore, clinical, paraclinical, and treatment data and follow up information was collected. Results A total of 16 patients (8 UESL, 8 HMH) were studied in this investigation. Patients with UESL had a significantly (p = 0.002) higher age at diagnosis compared with those with HMH. Histologically, UESL cases were characterized by anaplastic cells with eosinophilic cytoplasm and bizarre nuclei and frequent atypical mitosis and spindling in a myxoid stroma while disordered arrangement of hepatic parenchyma, bile ducts, and primitive mesenchyme was seen in HMH. Furthermore, small round cells and extramedullary hematopoiesis were seen in 2 UESL and 3 HMH cases, respectively. Concurrent HMH was also seen in two UESL cases. Immunohistochemistry panel showed positive staining for Vimentin, Glypican-3, Desmin, CD56, CD10, and BCL2 in UESL cases and immunoreactivity for Vimentin, HepPar 1, Glypican-3, SMA, CD56, BCL2, and CD34 in various components of HMH. Conclusions In this study, the clinicopathologic features of UESL and HMH cases are presented. We also evaluated the utility of an immunohistochemistry panel in the diagnosis of these two rare entities and suggested novel markers. Our study corroborated the findings of previous investigations and expanded the clinicopathologic features of these two rare entities with diagnostic and potential therapeutic implications.